Risk factors of cardiac allograft vasculopathy - Szyguła-Jurkiewicz, Bożena; Szczurek, Wioletta; Gąsior, Mariusz; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Despite advances in prevention and treatment of heart transplant rejection, development of cardiac allograft vasculopathy (CAV) remains the leading factor limiting long-term survival of the graft. Cardiac allograft vasculopathy etiopathogenesis is not fully understood, but a significant role is attributed to endothelial cell damage, caused by immunological and non-immunological mechanisms. Immunological factors include the differences between the recipient’s and the donor’s HLA systems, the presence of alloreactive antibodies and episodes of acute rejection. Among the non-immunological factors the most important are the age of the donor, ischemia-reperfusion injury and cytomegalovirus infection. The classical cardiovascular risk factors (diabetes, hypertension, obesity and hyperlipidemia) are also important. This study presents an up-to-date overview of current knowledge on the vasculopathy etiopathogenesis and the role played by endothelium and inflammatory processes in CAV, and it also investigates the factors which may serve as risk markers of cardiac allograft vasculopathy.